Digital Literacy Assistance to the Sei Lekop Fish Crackers Industry Centre as an Effort to Develop Business and Upgrade MSMEs - Tetty, Tetty; Hafsar, Khairul; Ulfah, Fitria; Haidawati, Haidawati; Zen, Linda Waty; Khairunnisa, Khairunnisa; Reni, Angga (Sarana Ilmu Indonesia (salnesia), 2025)
The high volume of captured fisheries is utilized by coastal communities as a livelihood source by processing the catch into value-added products such as fish crackers. This community service program aimed to improve the digital literacy of micro, small, and medium enterprise (MSME) actors to support business development and MSME advancement. Conducted from April to November 2024 at the Sei Lekop Fish Crackers Industry Center in Bintan Regency, the program targeted seven Joint Business Groups (Kelompok Usaha Bersama/KUBE), with two participants each. However, one participant was absent, resulting in 13 total attendees.The program responded to key challenges such as continued reliance on conventional marketing and limited access to digital platforms. Products were often resold without proper branding, and customers struggled to find them online due to participants’ limited knowledge of digital marketing and time constraints in managing e-commerce. To address these issues, the program included educational sessions and hands-on mentoring in digital literacy. The implementation followed three phases: preparation, execution, and evaluation. Training covered creating social media and e-commerce accounts, as well as content creation using tools like Canva. The evaluation used pre- and post-program questionnaires to measure changes in understanding. Results showed a significant increase in digital literacy among participants, from an average of 36.93% before the program to 63.07% after. This indicates that the intervention effectively enhanced the digital capacity of MSME actors, supporting their business sustainability and competitiveness in the digital era.